Outcomes of Children Treated With Tracheostomy and Positive-Pressure Ventilation at Home. (January 2013) - Com, Gulnur; Kuo, Dennis Z.; Bauer, Martin L.; Lenker, Claire V.; Melguizo-Castro, Maria M.; Nick, Todd G.; Makris, Christopher M.
Background . Long-term outcomes for children who survive on tracheostomy and positive-pressure ventilation (TPPV) at home are not well known. Methods . A retrospective review of 20 years of clinical data at a single institution was performed. Outcome measures included 5-year survival, decannulation rate, and neurocognition. Results . A total of 91 children were categorized under neuromotor dysfunction (52%), chronic lung disease (29%), and congenital anomalies (20%). The 5-year survival rates for these categories were 89% (95% confidence interval [CI] = 80%-99%), 76% (95% CI = 57%-100%), and 94% (95% CI = 83%-100%), respectively. Overall, the 5-year decannulation rate was 25% (95% CI = 14%-35%), with children with chronic lung disease having the highest rate (51%). It was found that 14% were extremely delayed in neurocognition. Conclusion . Most children on TPPV at home survive beyond 5 years, and a significant number are decannulated. Primary care physicians and communities should be prepared to accommodate the increasing number of children on TPPV at home.